Disease map-based biomarker selection and pre-validation for bladder cancer diagnostic. (July 2015) - De Paoli, Marine; Perco, Paul; Mühlberger, Irmgard; Lukas, Arno; Pandha, Hardev; Morgan, Richard; Feng, Gui Jie; Marquette, Christophe
Abstract Context: Urinary biomarkers are promising as simple alternatives to cystoscopy for the diagnosis of de novo and recurrent bladder cancer. Objective: To identify a highly sensitive and specific biomarker candidate set with potential clinical utility in bladder cancer. Materials and methods: Urinary biomarker concentrations were determined by ELISA. The performance of individual markers and marker combinations was assessed using ROC analysis. Results: A five-biomarker panel (IL8, MMP9, VEGFA, PTGS2 and EN2) was defined from the candidate set. Discussion and conclusion: This panel showed a better overall performance than the best individual marker. Further validation studies are needed to evaluate its clinical utility in bladder cancer.